Tinjauan Literatur Sistematis terhadap Pengalaman Wisatawan dalam Kegiatan Wisata Halal - Samsudin Arifin Dabamona (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2022)
The development of the tourism industry cannot be separated from its relationship with the experience of tourists who have been involved at an emotional, physical, intellectual, or even spiritual level. Halal tourism is unique and different because the tourist experience becomes bound by Islamic laws and regulations. This research is a literature review study that aims to map and reflect on the literature based on academic databases in the field of halal tourism and tourist experiences. Using a content analysis approach to 51 academic writings, this study illustrates the distribution of tourists and halal tourism, provides context in scientific disciplines and focuses on geographic coverage and an overview of the tourist experience based on typology. The results of the study indicate some areas that are still underexplored and recommend solutions to solve them.